Gli incontri di preparazione al matrimonio: importenza, difficoltà e spunti di soluzione - Cattaneo, Arturo ("Iustitia et iudicium" ; 1, 2010)
As we are witnesses to a progressive deterioration of the concept of family and a corrosion of matrimonial values, the need for improved marriage preparation constituts an important pastoral challenge. This reflection aims to examine some of the major difficulties related to such encounters, namely: difficulties arising from the different grades of preparation of the participants, the need not to limit the programme to passing on information but also to aim to the discover and clarify the Catholic teaching with regard to nuptial life and its values